Freedom of information and law - Narayana, P.S. (Hyderabad, 2004)
In a democratic system, every citizen has a right to information i.e., the right to know about the functioning of the public institution which helps in transparency and accountability of the government. The Judiciary in India has recognised the right to information as a fundamental right in recent times, followed by certain States which enacted specific legislations on the subject. The Freedom of Information Act, 2002, passed by the Parliament recently is a land- mark legislation in the annals of Indian Legal History. This Book is the result of a sincere effort to present to the readers a wide spectrum of issues relating to freedom of information in India like evolution of the right in India, position in International Law and other countries, judicial interpretation, position under the Indian Constitution, the Indian Evidence Act and the Official Secrets Act, and right to Privacy. It contains a sectionwise commentary on the Freedom of Information Act, 2002, apart from incorporating the similar legislations in some of the states like Tamil Nadu, Karnataka and Goa. This book is a valuable addition to the Libraries of the Courts, Advocates, Public Authorities, Universities and Law Schools and the individuals concerned with the subject.
Keywords: Right to information